Dampak Investasi Asing di Pulau Komodo - Satrya Mutthaqin, Muhammad; Rafiqoh Lubis, Nurul; Batubara, Maryam (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Komodo Island, as Indonesia's famous tourism destination, has attracted foreign investment which has the potential to influence the economic, social and environmental sectors. This investment brings benefits in the form of opening jobs, increasing local community income, and developing tourism infrastructure. However, the impact also creates economic disparities between local and foreign workers, as well as social problems related to cultural interactions and local community access to the benefits of tourism. Meanwhile, developing tourist infrastructure also threatens the Komodo dragon habitat and the Komodo Island ecosystem. Therefore, mitigation measures are needed to ensure foreign investment supports sustainable development and preservation of the Komodo Island ecosystem. This research uses a literature review method which involves analysis from various sources such as scientific journals, books, reports and articles related to the impact of foreign investment on Komodo Island. This research aims to analyze the impact of foreign investment on Komodo Island on the economic, social and environmental sectors. The research focus includes discussing the economic impact through opening jobs and increasing income, the social impact related to cultural interactions, and the environmental impact of tourism infrastructure development.